Biomechanical evaluation of DTRAX® posterior cervical cage stabilization with and without lateral mass fixation - Voronov LI (Dove Medical Press, 2016)
Leonard I Voronov,1,2 Krzysztof B Siemionow,3 Robert M Havey,1,2 Gerard Carandang,2 Avinash G Patwardhan1,2 1Department of Orthopaedic Surgery and Rehabilitation, Loyola University Chicago, Maywood, 2Musculoskeletal Biomechanics Laboratory, Edward Hines Jr. VA Hospital, Hines, 3Department of Orthopaedics, University of Illinois College of Medicine at Chicago, Chicago, IL, USA Introduction: Lateral mass screw (LMS) fixation with plates or rods is the current standard procedure for posterior cervical fusion. Recently, implants placed between the facet joints have become available as an alternative to LMS or transfacet screws for patients with cervical spondylotic radiculopathy. The purpose of this study was to evaluate the biomechanical stability of the DTRAX® cervical cage for single- and two-level fusion and compare this to the stability achieved with LMS fixation with rods in a two-level construct.Methods: Seven cadaveric cervical spine (C3–C7) specimens were tested in flexion–extension, lateral bending, and axial rotation to ±1.5 Nm moment without preload (0 N) in the following conditions: 1) intact (C3–C7), 2) LMS and rods at C4–C5 and C5–C6, 3) removal of all rods (LMS retained) and placement of bilateral posterior cages at C5–C6, 4) bilateral posterior cages at C4–C5 and C5–C6 (without LMS and rods), and 5) C4–C5 and C5–C6 bilateral posterior cages at C4–C5 and C5–C6 with rods reinserted.Results: Bilateral posterior cervical cages significantly reduced range of motion in all tested directions in both single- and multilevel constructs (P<0.05). Similar stability was achieved with bilateral posterior cages and LMS in a two-level construct: 0.6°±0.3° vs 1.2°±0.4° in flexion–extension (P=0.001), (5.0°±2.6° vs 3.1°±1.3°) in lateral bending (P=0.053), (1.3°±1.0° vs 2.2°±0.9°) in axial rotation (P=0.091) for posterior cages and LMS, respectively. Posterior cages, when placed as an adjunct to LMS, further reduced range of motion in a multilevel construct (P<0.05).Conclusion: Bilateral posterior cages provide similar cervical segmental stability compared with a LMS and rod construct and may be an alternative surgical option for select patients. Furthermore, supplementation of a lateral mass construct with posterior cages increases cervical spine stability in single- and multilevel conditions. Keywords: cervical spine, posterior fusion, biomechanics, cervical facets, DTRAX cervical cage, lateral mass screw